Export credit and credit insurance facilities in India and abroad - Verghese, S. K. (New Delhi : Indian Institute of Foreign Trade, 1970)
This book is on medium and long term export credit which are partly financed by supplier credit and partly by buyers.
oo 22/01/2019
Loans
Keywords: Export credit; Credit; Credit insurance; India